2013
DOI: 10.4049/jimmunol.1202435
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Ly9 (CD229), a SLAM Family Receptor, Negatively Regulates the Development of Thymic Innate Memory-like CD8+ T and Invariant NKT Cells

Abstract: Signaling lymphocytic activation molecule family (SLAMF) receptors and the specific adapter SLAM-associated protein (SAP) modulate the development of innate-like lymphocytes. Here, we show that the thymus of Ly9-deficient mice contains an expanded population of CD8 single-positive cells with the characteristic phenotype of innate memory-like CD8+ T-cells. Moreover, the proportion of these innate CD8+ T-cells increased dramatically after infection with mouse cytomegalovirus. Gene expression profiling of Ly9-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 17 publications
4
45
1
Order By: Relevance
“…As previously reported (20, 22), we found that the homotypic SAP-dependent receptors Slamf1, Slamf3, Slamf5, and Slamf6 are moderately to highly expressed by DP TCRβ low thymocytes. Although Slamf2 is highly expressed by these cells, its receptor, Slamf4, is virtually absent, suggesting that this heterophilic interaction does not play a role during homotypic DP-DP contacts (Figure S1D in Supplementary Material).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As previously reported (20, 22), we found that the homotypic SAP-dependent receptors Slamf1, Slamf3, Slamf5, and Slamf6 are moderately to highly expressed by DP TCRβ low thymocytes. Although Slamf2 is highly expressed by these cells, its receptor, Slamf4, is virtually absent, suggesting that this heterophilic interaction does not play a role during homotypic DP-DP contacts (Figure S1D in Supplementary Material).…”
Section: Resultssupporting
confidence: 89%
“…Cognate activation of NKT cells is restricted to CD1d–lipid complexes and is modulated by SAP and at least three members of the SLAMF of receptors (2022). The homophilic interactions of Slamf1 and Slamf6 between DP thymocytes are particularly important for the development of the NKT cell lineage (20).…”
Section: Introductionmentioning
confidence: 99%
“…The link between SLAMF3 expression and proliferation was demonstrated in vitro and then validated by the inhibition of HCC progression in Nude mice xenografted with SLAMF3-overexpressing HCC cells. It was recently reported that SLAMF3 has a similar role in lymphocytes; in contrast to SLAMF1 and SLAMF6, SLAMF3 has a negative effect on the signalling pathways required for innate-like lymphocyte development in the thymus [37]. The observed effect may be attributed to both decrease in the proliferation of cells over-expressing SLAMF3 and the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the Slamf8-deficient mice have normal iNKT cell numbers but with an enlarged PLZF hi iNKT2 compartment [64]. Because the Slamf8 molecules signal independently of SAP and Slamf8-encoding mRNA is expressed in dendritic cells and fibroblasts in the thymus but not DP thymocytes, it is likely that Slamf8 functions differently than the other Slam-family molecules in affecting iNKT cell development [30,64,65,66]. Instead, these results suggest that DC cells or fibroblasts might provide external signals, which are affected by the absence of Slamf8, to developing iNKT cells.…”
Section: Cell Extrinsic Signalsmentioning
confidence: 99%